Polyurethane adhesive and preparation method thereof
By adding modified biomass and other additives to the aqueous polyurethane adhesive and adopting light induction and vacuum heat sealing processes, the problems of insufficient initial adhesion and poor water resistance of the aqueous polyurethane adhesive are solved, and the problem of insufficient water resistance is achieved. Polyurethane adhesives with high bond strength and water resistance.
Patent Information
- Application Number
- CN202411747355.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-14
AI Technical Summary
The initial adhesion of unmodified water-based polyurethane adhesive is weak, which affects the construction effect. It also contains hydrophilic groups on the molecular chain, resulting in poor water resistance.
Modified biomass is prepared by mixing epoxidized tannins and modified aloe in a certain proportion to form modified biomass, and combined with flame retardant, antistatic additive, water-resistant additive and crosslinking agent. A polyurethane adhesive. The adhesive promotes its crosslinking reaction through processes such as light induction and vacuum heat sealing, and improves its bonding strength and water resistance.
It improves the bonding strength and water resistance of polyurethane adhesives, enhances its stability and durability in high temperatures and various environments, reduces the risk of allergic reactions, and is suitable for bonding on surfaces of multiple materials.
Smart Images

Figure CN119432296A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane adhesives, and in particular to a polyurethane adhesive and a preparation method thereof. Background Art
[0002] Textile adhesives are chemicals widely used in the textile industry. They can improve the bonding performance between fibers and enhance the durability and functionality of fabrics. According to different application scenarios and requirements, textile adhesives can be divided into many types, including slurries, paint printing adhesives, adhesives for non-woven fabrics, electrostatic flocking adhesives, adhesives for coating and finishing of fabrics, adhesives for pasting textiles, hot melt adhesives for textiles, and polyacrylate emulsion adhesives.
[0003] Water-based polyurethane adhesives use water as a solvent, which reduces pollution to the environment, meets environmental protection requirements, helps improve indoor air quality, and can achieve strong bonding on a variety of different material surfaces, including metal, plastic, paper, cloth, etc. It has high bonding strength, can withstand greater stress and load, and can maintain stable bonding performance in high temperature environments. It is not easy to melt or decompose, and can also resist the erosion of ultraviolet rays, humidity and chemicals.
[0004] However, the initial adhesion of unmodified waterborne polyurethane adhesive is weak, which affects the construction effect, and due to the presence of hydrophilic groups on the molecular chain, its water resistance is poor.
[0005] Therefore, the present invention decides to develop a polyurethane adhesive to solve the above problems. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a polyurethane adhesive and a preparation method thereof.
[0007] A polyurethane adhesive, comprising the following components by mass percentage:
[0008] Modified biomass: 20-30%;
[0009] Flame retardant: 0.5-1%;
[0010] Antistatic additive: 1-2%;
[0011] Water resistance additive: 1-2%;
[0012] Cross-linking agent: 2-4%;
[0013] Waterborne polyurethane: balance;
[0014] The modified biomass is a mixed biomass obtained by mixing epoxidized tannin and modified aloe vera in a mass ratio of 1:1 to 2.
[0015] Furthermore, the method for preparing the modified biomass comprises the following steps:
[0016] Add tannin to an aqueous solution of epichlorohydrin with a molar concentration of 1.5-2 mol / L, heat to 82-85°C, react for a period of time, add a 20% NaOH aqueous solution, keep the temperature to react for 1.5-2.5 hours, cool to room temperature, repeat dilution with anhydrous ethanol and acetone, filter, and rotary evaporate for 3-5 times to obtain epoxidized tannin;
[0017] The aloe vera is crushed and dried to obtain aloe vera powder, and steam exploded at a pressure of 3 to 5 MPa for 4 to 6 minutes, and then reduced to atmospheric pressure to obtain aloe vera fiber; and the aloe vera fiber is added to deionized water at a solid-liquid ratio of 1 g: 8 to 10 mL, stirred at room temperature for 30 to 40 minutes, and then heated to 50 to 55° C., revolved at 80 to 100 r / min, and rotated at 700 to 800 r / min for 20 to 30 minutes; then heated to 65 to 75° C., 4 to 5% of phenyltrimethylammonium chloride by weight of the aloe vera powder is added, the aloe vera powder is revolved at 40 to 60 r / min, and rotated at 300 to 400 r / min for 10 to 15 minutes, and then cooled to 50 to 55° C., 0.5 to 1% of 1-vinyl-2-pyrrolidone by weight of the aloe vera powder is added, and the container is closed and placed at a constant temperature of 40 to 45° C. and stirred for 2 to 3 hours to obtain modified aloe vera;
[0018] After mixing the epoxidized tannin and the modified aloe vera in the stated proportion, the mixture is placed in a reactor at 110-120° C. for reaction for 1.5-3 hours to obtain modified biomass.
[0019] Description: Due to its polyphenol structure, epoxidized tannin can form strong hydrogen bonds and covalent bonds with the surfaces of various materials, thereby enhancing adhesion. The epoxy groups of epoxidized tannin can form stable hydrogen bonds with water molecules, reducing the destructive effect of water on the adhesive and improving the water resistance of the adhesive. Aloe vera contains some sticky substances, which help to improve the viscosity and durability of the adhesive. Phenyltrimethylammonium chloride can also improve the stability and durability of the fiber, making it more durable in various environments. Adding 1-vinyl-2-pyrrolidone to aloe vera fiber can promote the bonding between aloe vera fiber and epoxidized tannin, and improve the mechanical strength and stability of the fiber. In the modification process, the fiber is first rotated at a low speed to reduce fiber damage caused by excessive mechanical stress. High temperature can usually accelerate chemical reactions, which helps the modifier to better combine with the fiber. Epoxidized tannins are cross-linked with active chemical components in aloe vera (such as polyphenol compounds), which can enhance their stability and antioxidant properties.
[0020] Furthermore, the flame retardant is polyarylene sulfide.
[0021] Description: Polyarylene sulfide can significantly improve the heat resistance of waterborne polyurethane adhesives, enabling them to maintain stable bonding performance at higher temperatures. The chemical stability of polyarylene sulfide helps to improve the adhesive's resistance to various chemicals and extend the adhesive's service life.
[0022] Furthermore, the antistatic auxiliary agent is any one of cocamidopropyl betaine, polyoxyethylene ether and sodium fatty acid diester sulfonate.
[0023] Description: In addition to the antistatic effect of the above reagents, cocamidopropyl betaine can reduce the surface tension of water-based polyurethane adhesives, improve their wettability and permeability, thereby improving the adhesive's ability to adhere to the surfaces of various materials; in addition, it can also be used as an emulsifier to help the particles in the water-based polyurethane dispersion to be evenly distributed, prevent agglomeration, and improve the stability of the adhesive; polyoxyethylene ether can also be used as a thickener and stabilizer to increase the viscosity and stability of water-based polyurethane adhesives; sodium fatty acid diester sulfonate can provide good lubricity and wettability, which helps the fluidity and uniformity of water-based polyurethane adhesives during the coating process.
[0024] Furthermore, the water resistance additive is VAE emulsion or XF-5003 fluorine-free waterproofing agent.
[0025] Description: VAE emulsion has good elasticity and toughness, and can provide stable bonding performance. The adhesive film formed by VAE emulsion has good water resistance and acid and alkali resistance, and is suitable for humid environments; XF-5003 fluorine-free waterproofing agent can effectively prevent moisture penetration, improve the water resistance of the adhesive, and has good compatibility with water-based polyurethane adhesives, and will not affect the original bonding performance.
[0026] Furthermore, the cross-linking agent is polyethylene glycol diamine-alginate modified SOD enzyme.
[0027] Description: The introduction of SOD enzyme will affect the interaction between waterborne polyurethane and modified aloe vera through its biological activity, thereby enhancing the bonding strength of the final product. The stability of the modified SOD enzyme will be transferred to the waterborne polyurethane and modified aloe vera, so that the final polyurethane adhesive has better durability and anti-aging properties.
[0028] A method for preparing a polyurethane adhesive as described in any one of the above, comprising the following steps:
[0029] S1, mixing waterborne polyurethane and flame retardant in proportion by light induction to obtain pretreated waterborne polyurethane;
[0030] The light induced by the light is ultraviolet light with a wavelength of 300 to 550 nm and a light intensity of 1 to 12 mW / cm 2, the illumination time is 50~600s;
[0031] S2, vacuum heat-sealing and mixing the pretreated waterborne polyurethane obtained in S1, the modified biomass, and the cross-linking agent in proportion to obtain a cross-linked product;
[0032] The vacuum heat sealing time is 45 to 55 seconds, the heat sealing time is 5 to 8 seconds, and the heat sealing temperature is 70 to 130°C.
[0033] S3, mixing the cross-linked product obtained in S2 with an antistatic agent and a water-resistant agent to obtain a polyurethane adhesive.
[0034] Furthermore, in step S3, the mixing is first performed at 250-350 MPa, orbital speed at 30-40 r / min, and rotation at 400-600 r / min, and mixing for 10-15 min; and then at 600-700 MPa, orbital speed at 60-70 r / min, and rotation at 800-900 r / min, and mixing for 5-10 min.
[0035] Note: Rotating at low speed under low pressure first helps ensure that all materials are fully mixed and improves the uniformity of mixing; rotating at high pressure and high speed can shorten the processing time and improve the overall mixing efficiency.
[0036] Compared with the existing polyurethane adhesive, the beneficial effects of the present invention are:
[0037] (1) The polyurethane adhesive of the present invention uses water-based polyurethane as the main component, which reduces pollution to the environment, meets environmental protection requirements, helps improve indoor air quality, and can achieve firm bonding on the surfaces of a variety of different materials, including metal, plastic, paper, cloth, etc. It has high bonding strength, can withstand large stress and load, and can maintain stable bonding performance under high temperature environment, is not easy to melt or decompose, and can also resist the erosion of ultraviolet rays, humidity and chemicals; and the modified biomass is added to the polyurethane adhesive. Aloe vera has good hydrophilicity, which can help improve the hydrophilicity of the water-based polyurethane adhesive and reduce skin irritation caused by dryness, thereby reducing the risk of allergic reactions; since aloe vera has a certain biocompatibility, its mixture with epoxidized tannin may make the polyurethane adhesive more suitable for contact with biological materials, such as medical devices or biomedical applications, and epoxidized tannin and modified aloe vera may improve the anti-aging performance of the polyurethane adhesive through antioxidant and anti-ultraviolet effects.
[0038] (2) In the method for preparing a polyurethane adhesive of the present invention, water-based polyurethane and a flame retardant are first light-induced mixed. Under light-induced conditions, the polyurethane and polyarylene sulfide can be quickly cured by light after being mixed, which greatly shortens the curing time and improves production efficiency; and the light-induced curing can effectively promote the cross-linking reaction between the polyurethane and the polyarylene sulfide, enhance the bonding strength and heat resistance, and make the adhesive more durable and stable; then the pretreated water-based polyurethane and the modified biomass are vacuum-heat-sealed and mixed, which can promote the cross-linking reaction between the water-based polyurethane and the modified biomass, enhance the properties of the adhesive, such as bonding strength, water resistance and chemical resistance, and improve the heat resistance and chemical resistance of the adhesive, so that it has a wider range of applicability and versatility in different application occasions. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a tensile strength comparison diagram of the present invention's exploration 1;
[0040] Figure 2 It is a comparison chart of water resistance of the present invention's exploration 1;
[0041] Figure 3 It is a comparison chart of tensile strength of the present invention 2;
[0042] Figure 4 It is a water resistance comparison chart of the present invention's exploration 2. DETAILED DESCRIPTION
[0043] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0044] Embodiment 1: A polyurethane adhesive, comprising the following components by mass percentage:
[0045] Modified biomass: 25%;
[0046] Flame retardant: 0.8%;
[0047] Antistatic additive: 1.5%;
[0048] Water resistance additive: 1.5%;
[0049] Cross-linking agent: 3%;
[0050] Waterborne polyurethane: balance;
[0051] The modified biomass is a mixed biomass obtained by mixing epoxidized tannin and modified aloe vera in a mass ratio of 1:1.5; the flame retardant is polyarylene sulfide, the antistatic agent is cocamidopropyl betaine, the water resistance agent is VAE emulsion, and the crosslinking agent is polyethylene glycol diamine-alginate modified SOD enzyme.
[0052] The preparation method of the modified biomass comprises the following steps:
[0053] Add tannin to an aqueous solution of epichlorohydrin with a molar concentration of 1.8 mol / L, heat it to 84°C, react for a period of time, add a 20% NaOH aqueous solution, keep the temperature to react for 2 hours, cool it to room temperature, repeat dilution with anhydrous ethanol and acetone, filter and rotary evaporate for 4 times to obtain epoxidized tannin;
[0054] The aloe vera is crushed and dried to obtain aloe vera powder, and the drying is spray drying, the air inlet temperature is 140°C, the air outlet temperature is 70°C, steam explosion is performed at a pressure of 4Mpa for 5 minutes, and then the pressure is reduced to atmospheric pressure to obtain aloe vera fiber; and the aloe vera fiber is added to deionized water at a solid-liquid ratio of 1g:9mL, stirred at room temperature for 35 minutes, then heated to 53°C, revolved at 90r / min, rotated at 750r / min, and treated for 25 minutes; then heated to 70°C, 4.5% of the mass of the aloe vera powder was added to phenyltrimethylammonium chloride, revolved at 50r / min, rotated at 350r / min, and treated for 13 minutes. The temperature was lowered to 53°C, 0.8% of the mass of the aloe vera powder was added to 1-vinyl-2-pyrrolidone, the container was closed and placed at a constant temperature of 43°C for stirring for 2.5 hours to obtain modified aloe vera; the instrument used for the revolution and rotation is a commercially available revolution and rotation integrated mixer;
[0055] After mixing the epoxidized tannin and the modified aloe vera in the above ratio, the mixture was placed in a reactor at 115° C. for reaction for 2 h to obtain modified biomass;
[0056] The preparation method of the waterborne polyurethane comprises the following steps:
[0057] Put the polyester diol into a reactor, vacuum dehydrate it at 100°C and -0.1MPa for 1.5 hours, and then cool it to 60°C; then add epoxidized polybutadiene resin and p-phenylene diisocyanate to the polyester diol in a mass ratio of 1:0.25:0.8, and react at 50°C for 2.5 hours to generate a polyurethane prepolymer;
[0058] Acetone accounting for 35% of the mass of the polyurethane prepolymer and dihydroxymethylsuccinic acid accounting for 9% of the mass of the polyurethane prepolymer are then added to react at 50°C for 2.5 hours to reduce the viscosity of the prepolymer; after cooling to 50°C or below, triethylamine accounting for 18% of the mass of the polyurethane prepolymer is added to obtain an ionomer; water accounting for 40% of the total mass of the waterborne polyurethane is added to the ionomer, and high-shear stirring and emulsification are performed for 2 minutes to obtain a waterborne polyurethane.
[0059] Embodiment 2: A method for preparing a polyurethane adhesive, comprising the following steps:
[0060] S1, mixing waterborne polyurethane and flame retardant, i.e., polyarylene sulfide, in a proportion by light induction to obtain a pretreated waterborne polyurethane;
[0061] The light induced by the light is ultraviolet light with a wavelength of 420nm and a light intensity of 6mW / cm 2 , the illumination time is 320s;
[0062] S2, vacuum heat-sealing and mixing the pretreated waterborne polyurethane obtained in S1, the modified biomass, and the cross-linking agent, namely, polyethylene glycol diamine-alginate modified SOD enzyme, in proportion to obtain a cross-linked product;
[0063] The vacuum heat sealing time is 50 seconds, the heat sealing time is 6 seconds, and the heat sealing temperature is 100°C.
[0064] S3, mixing the cross-linked product obtained in S2 with an antistatic auxiliary agent, namely cocamidopropyl betaine, and a water resistance auxiliary agent, namely VAE emulsion, to obtain a polyurethane adhesive;
[0065] The mixing is firstly carried out at 300 MPa, orbital rotation at 35 r / min, autorotation at 500 r / min, and mixing for 13 min; and then at 650 MPa, orbital rotation at 65 r / min, autorotation at 850 r / min, and mixing for 8 min.
[0066] Example 3: This example is different from Example 1 in that the polyurethane adhesive comprises the following components by mass percentage: modified biomass: 20%; flame retardant: 0.5%; antistatic agent: 1%; water resistance agent: 1%; cross-linking agent: 2%; water-based polyurethane: balance; the antistatic agent is polyoxyethylene ether, and the water resistance agent is XF-5003 fluorine-free waterproofing agent.
[0067] Example 4: This example is different from Example 1 in that the polyurethane adhesive comprises the following components by mass percentage: modified biomass: 30%; flame retardant: 1%; antistatic agent: 2%; water resistance agent: 2%; crosslinking agent: 4%; water-based polyurethane: balance; the antistatic agent is sodium fatty acid diester sulfonate.
[0068] Example 5: This example is different from Example 1 in that tannin is added to an aqueous solution of epichlorohydrin with a molar concentration of 1.5 mol / L, the temperature is raised to 82°C, and after reacting for a period of time, an aqueous solution of NaOH with a mass concentration of 20% is added. After the reaction is kept warm for 1.5 hours, the mixture is cooled to room temperature, diluted with anhydrous ethanol and acetone, filtered, and rotary evaporated three times to obtain epoxidized tannin.
[0069] Example 6: This example is different from Example 1 in that tannin is added to an aqueous solution of epichlorohydrin with a molar concentration of 2 mol / L, the temperature is raised to 85°C, and after reacting for a period of time, a 20% NaOH aqueous solution is added. After the reaction is kept warm for 2.5 hours, the mixture is cooled to room temperature, diluted with anhydrous ethanol and acetone, filtered, and rotary evaporated for 5 times to obtain epoxidized tannin.
[0070] Example 7: This example is different from Example 1 in that aloe vera is crushed and dried to obtain aloe vera powder, which is steam exploded at a pressure of 3 MPa for 4 min and then reduced to atmospheric pressure to obtain aloe vera fiber.
[0071] Example 8: This example is different from Example 1 in that aloe vera is crushed and dried to obtain aloe vera powder, which is steam exploded at a pressure of 5 MPa for 6 minutes and then reduced to atmospheric pressure to obtain aloe vera fiber.
[0072] Example 9: This example is different from Example 1 in that aloe fiber is added to deionized water at a solid-liquid ratio of 1 g:8 mL, phenyltrimethylammonium chloride is added at 4% by mass of the aloe powder, and 1-vinyl-2-pyrrolidone is added at 0.5% by mass of the aloe powder to obtain modified aloe.
[0073] Example 10: This example is different from Example 1 in that aloe fiber is added to deionized water at a solid-liquid ratio of 1 g:10 mL, phenyltrimethylammonium chloride accounting for 5% of the mass of aloe powder is added, and 1-vinyl-2-pyrrolidone accounting for 1% of the mass of aloe powder is added to obtain modified aloe.
[0074] Example 11: The difference between this example and Example 1 is that the mixture is stirred at room temperature for 30 minutes, then heated to 50°C, revolved at 80 r / min, rotated at 700 r / min, and treated for 20 minutes; then the temperature is raised to 75°C, revolved at 60 r / min, rotated at 400 r / min, and treated for 10 minutes, then cooled to 50°C, the container is closed and stirred at a constant temperature of 40°C for 2 hours.
[0075] Example 12: The difference between this example and Example 1 is that the mixture is stirred at room temperature for 40 minutes, then heated to 55°C, revolved at 100 r / min, rotated at 800 r / min, and treated for 30 minutes; then the temperature is raised to 65°C, revolved at 40 r / min, rotated at 300 r / min, and treated for 15 minutes, then cooled to 55°C, the container is closed and stirred at a constant temperature of 45°C for 3 hours.
[0076] Example 13: This example is different from Example 1 in that the epoxidized tannin and the modified aloe vera are mixed in a mass ratio of 1:1 and placed in a reactor at 110° C. for reaction for 1.5 h.
[0077] Example 14: This example is different from Example 1 in that the epoxidized tannin and the modified aloe vera are mixed in a mass ratio of 1:2 and placed in a reactor at 120° C. for reaction for 3 hours.
[0078] Example 15: This example is different from Example 2 in that the light-induced illumination is ultraviolet light with a wavelength of 300 nm and an illumination intensity of 1 mW / cm 2 , the illumination time is 50s.
[0079] Example 16: This example is different from Example 2 in that the light-induced illumination is ultraviolet light with a wavelength of 550 nm and an illumination intensity of 12 mW / cm 2 , the illumination time is 600s.
[0080] Example 17: This example is different from Example 2 in that the vacuuming time of vacuum heat sealing is 45 s, the heat sealing time is 5 s, and the heat sealing temperature is 70°C.
[0081] Example 18: This example differs from Example 2 in that the vacuum heat sealing time is 55 s, the heat sealing time is 8 s, and the heat sealing temperature is 130°C.
[0082] Example 19: The difference between this example and Example 2 is that in step S3, the mixing is first performed at 250 MPa, orbital revolution at 30 r / min, and autorotation at 400 r / min, and mixing for 10 min; then at 700 MPa, orbital revolution at 70 r / min, and autorotation at 900 r / min, and mixing for 5 min.
[0083] Example 20: The difference between this example and Example 2 is that in step S3, the mixing is first performed at 350 MPa, orbital revolution at 40 r / min, and autorotation at 600 r / min, and mixing for 15 min; then at 600 MPa, orbital revolution at 60 r / min, and autorotation at 800 r / min, and mixing for 10 min.
[0084] Experimental Example: The description of this experimental example is based on the scheme described in Example 2, and is intended to illustrate the practical application effect of the present invention.
[0085] The polyurethane adhesive is coated on the sample and the initial tensile strength is tested. The sample coated with the polyurethane adhesive is then immersed in water for 15 days and then its tensile strength is measured. The reduction rate of the tensile strength is calculated and the data from five tests is taken as the average value, which serves as data support for water resistance.
[0086] 1. To explore the influence of the proportion of each component of polyurethane adhesive and the preparation parameters of modified biomass on the tensile strength and water resistance of polyurethane adhesive.
[0087] The difference between Control Example 1 and Example 1 is that no modified biomass is added;
[0088] The difference between the control example 2 and the example 1 is that no revolution or rotation is applied, and only stirring treatment is performed;
[0089] Depend on Figure 1 and Figure 2 It can be seen that the control example 1 lacks the modified biomass and the control example 2 lacks the revolution and rotation treatment, and the tensile strength of the polyurethane adhesive is significantly reduced compared with Examples 1 to 14; and after the corresponding immersion, the reduction rate of the tensile strength of the polyurethane adhesive also increases, and the water resistance is reduced;
[0090] By comparing Examples 1 and 3 to 14, it can be seen that the proportion of modified biomass is too small or too large, the preparation parameters of epoxidized tannin are too small or too large, the parameters of steam explosion are too small or too large, the proportion of aloe fiber is too small or too large, the parameter change of revolution and rotation treatment is too small or too large, and the parameters of mixing epoxidized tannin and modified aloe are too small, which will reduce the tensile strength and water resistance of the polyurethane adhesive. In Example 14, due to the larger proportion of modified aloe, higher mixing temperature and longer time, the tensile strength and water resistance are improved compared with Example 1, but the improvement is small. Therefore, from an economic point of view, the parameter effect of Example 1 is relatively better.
[0091] 2. Investigate the influence of preparation parameters of polyurethane adhesive on the tensile strength and water resistance of polyurethane adhesive.
[0092] The difference between Control Example 3 and Example 2 is that no light induction is applied;
[0093] The difference between Comparative Example 4 and Example 2 is that vacuum heat sealing is not performed, but the temperature is directly increased and mixed;
[0094] The difference between the comparative example 5 and the example 2 is that no revolution or rotation is applied, and only stirring and mixing is performed;
[0095] Depend on Figure 3 and Figure 4 It can be seen that control example 3 lacks light induction, control example 4 lacks vacuum heat sealing, and control example 5 lacks revolution and rotation treatment, which significantly reduce the tensile strength and water resistance compared with examples 2 and 15 to 20;
[0096] By comparing Examples 2 and 15 to 20, it can be seen that too small or too large light-induced parameters, too small vacuum heat-sealing parameters, and too small or too large changes in revolution and rotation parameters will reduce the tensile strength and water resistance of the polyurethane adhesive. In Example 18, since the vacuum heat-sealing time is longer and the temperature is higher, the tensile strength and water resistance are improved compared to Example 2, but the improvement is small. Therefore, from an economic point of view, the parameter effect of Example 2 is relatively better.
[0097] In summary, the tensile strength of the polyurethane adhesive prepared by the present invention can reach above 3.0 MPa, and the reduction rate of the tensile strength after immersion is less than 13.8%, that is, the polyurethane adhesive has good bonding performance and water resistance.
Claims
1. A polyurethane adhesive, characterized in that: Calculated by mass percentage, it includes the following components: Modified biomass: 20-30%; Flame retardant: 0.5-1%; Antistatic additive: 1-2%; Water resistance additive: 1-2%; Cross-linking agent: 2-4%; Waterborne polyurethane: balance; The modified biomass is a mixed biomass obtained by mixing epoxidized tannin and modified aloe vera in a mass ratio of 1:1 to 2.
2. A polyurethane adhesive as claimed in claim 1, characterized in that: The preparation method of the modified biomass comprises the following steps: Add tannin to an aqueous solution of epichlorohydrin with a molar concentration of 1.5-2 mol / L, heat to 82-85°C, react for a period of time, add a 20% NaOH aqueous solution, keep the temperature to react for 1.5-2.5 hours, cool to room temperature, repeat dilution with anhydrous ethanol and acetone, filter, and rotary evaporate for 3-5 times to obtain epoxidized tannin; The aloe vera is crushed and dried to obtain aloe vera powder, and steam exploded at a pressure of 3 to 5 MPa for 4 to 6 minutes, and then reduced to atmospheric pressure to obtain aloe vera fiber; and the aloe vera fiber is added to deionized water at a solid-liquid ratio of 1 g: 8 to 10 mL, stirred at room temperature for 30 to 40 minutes, and then heated to 50 to 55° C., revolved at 80 to 100 r / min, and rotated at 700 to 800 r / min for 20 to 30 minutes; then heated to 65 to 75° C., 4 to 5% of phenyltrimethylammonium chloride by weight of the aloe vera powder is added, the aloe vera powder is revolved at 40 to 60 r / min, and rotated at 300 to 400 r / min for 10 to 15 minutes, and then cooled to 50 to 55° C., 0.5 to 1% of 1-vinyl-2-pyrrolidone by weight of the aloe vera powder is added, and the container is closed and placed at a constant temperature of 40 to 45° C. and stirred for 2 to 3 hours to obtain modified aloe vera; After mixing the epoxidized tannin and the modified aloe vera in the stated proportion, the mixture is placed in a reactor at 110-120° C. for reaction for 1.5-3 hours to obtain modified biomass.
3. A polyurethane adhesive as claimed in claim 1, characterized in that: The flame retardant is polyarylene sulfide.
4. A polyurethane adhesive as claimed in claim 1, characterized in that: The antistatic auxiliary agent is any one of cocamidopropyl betaine, polyoxyethylene ether and sodium fatty acid diester sulfonate.
5. A polyurethane adhesive as claimed in claim 1, characterized in that: The water resistance auxiliary agent is VAE emulsion or XF-5003 fluorine-free waterproofing agent.
6. A polyurethane adhesive as claimed in claim 1, characterized in that: The cross-linking agent is polyethylene glycol diamine-alginate modified SOD enzyme.
7. The method for preparing a polyurethane adhesive according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, mixing waterborne polyurethane and flame retardant in proportion by light induction to obtain pretreated waterborne polyurethane; The light induced by the light is ultraviolet light with a wavelength of 300 to 550 nm and a light intensity of 1 to 12 mW / cm 2 , the illumination time is 50~600s; S2, vacuum heat-sealing and mixing the pretreated waterborne polyurethane obtained in S1, the modified biomass, and the cross-linking agent in proportion to obtain a cross-linked product; The vacuum heat sealing time is 45 to 55 seconds, the heat sealing time is 5 to 8 seconds, and the heat sealing temperature is 70 to 130°C. S3, mixing the cross-linked product obtained in S2 with an antistatic agent and a water-resistant agent to obtain a polyurethane adhesive.
8. The method for preparing a polyurethane adhesive according to claim 7, characterized in that: In step S3, the mixing is firstly carried out at 250-350 MPa, orbital speed at 30-40 r / min, autorotation at 400-600 r / min, and mixing for 10-15 min; and then at 600-700 MPa, orbital speed at 60-70 r / min, autorotation at 800-900 r / min, and mixing for 5-10 min.
9. The method for preparing a polyurethane adhesive according to claim 7, characterized in that: The light induced by light is ultraviolet light with a wavelength of 300-550nm and a light intensity of 1-12mW / cm 2 , the illumination time is 50 to 600 seconds.